Economic policy for a social Europe. A critique of neo-liberalism and proposals for alternatives - Huffschmid, Jörg (Basingstoke, 2005)
"This book poses a critique of neoliberal economic polices in the EU and proposals for alternatives. The book argues that the economic weakness of the EU is the result of the very restrictive economic policy of the Union and most member states. The book advances from a comprehensive critique of macroeconomic, social and structural policies towards a concrete concept for a democratic European social model based on the objectives of full employment, welfare, social equity and ecological sustainability."